United Nations participants in the Korean War the contributions of 45 member countries - Edwards, Paul M. (McFarland, 2013)
" When in 1950 the United Nations called upon its members to provide aid to South Korea, 45 nations responded. Some sent troops, some sent commodities and medical supplies, some political support but not aid. This book looks at the nations involved, what was behind their willingness to provide troops or aid, or what prevented them"--